Multitheoretical Analysis of Taxpayer Compliance in the Coretax Era - Paulus, Hendro; Apollo Daito (Jurnal Akuntansi, 2026)
Tax compliance plays an important role in supporting state revenue, which is used to finance development and provide public services. Although the government has implemented tax reforms by simplifying the administrative system and implementing Coretax, the level of corporate taxpayer compliance in Indonesia still faces various challenges, including limited understanding of taxation, suboptimal effectiveness of sanctions, and technical obstacles in implementation. This study aims to analyze the influence of tax knowledge, tax sanctions, and Coretax implementation on corporate taxpayer compliance, with tax socialization as a moderating variable. Data were obtained from 400 corporate taxpayers registered at the Jakarta Pademangan Tax Office through random sampling and analyzed using Structural Equation Modeling (SEM) based on SMARTPLS 3.2.9. The results show that tax knowledge and sanctions have a positive effect on compliance, while Coretax has no direct effect. Tax socialization strengthens the influence of knowledge and Coretax, but weakens the influence of tax sanctions.